DETEKSI DINI DAN PENANGANAN KATARAK DALAM MENJAGA FUNGSI PENGLIHATAN: SCOPING REVIEW DAN PERSPEKTIF AL-ISLAM KEMUHAMMADIYAHAN - Bagus Tri Prakoso; Z.A. Saraswati Dewi Utari; Annisa Safa’atul Azizah; Samsi Ardiansyah; Muhammad Fadhil Ramadhan; Nadia Nadia; Moh. Atha Fadlian Tito Marstin; Yusuf Maulana Alfatah; Assyamsy Fallakg Vijayanathan; Muhammad Gamis Ghozali (Jurnal Kesehatan dan Pembangunan, 2026)
Cataract is a leading cause of preventable visual impairment and blindness worldwide, with increasing life expectancy continuing to raise the number of cataract patients, making early detection and appropriate management crucial strategies, and this study aims to map scientific evidence on risk factors, early detection methods, and cataract management while examining their relevance from the perspective of Al-Islam and Kemuhammadiyahan. The method used was a scoping review following PRISMA-ScR guidelines with literature searches conducted in Google Scholar, PubMed, and ScienceDirect from 2013 to 2024 using keywords including cataract, early detection, screening, management, and treatment, where selection was performed by two independent reviewers and twenty articles were analyzed using thematic synthesis. The results showed that main risk factors include advanced age, diabetes mellitus, hypertension, obesity, smoking, and ultraviolet exposure, while early detection methods include visual acuity examination, slit-lamp biomicroscopy, red reflex test, and artificial intelligence-based technology with accuracy up to 99%, and phacoemulsification surgery remains the main treatment with a success rate >90%. From an Islamic perspective, maintaining visual health is part of hifdz al-nafs and ikhtiar, which aligns with the values of amar ma'ruf, ta'awun, and tajdid within Kemuhammadiyahan, leading to the conclusion that timely early detection and management of cataract play an important role in preventing blindness, and integration of medical, educational, social, and spiritual approaches based on Al-Islam and Kemuhammadiyahan values has the potential to strengthen the success of cataract prevention and control programs in the community.